Mediator proteins orchestrate enzyme-ssDNA assembly during T4 recombination-dependent DNA replication and repair - Bleuit, Jill S. (The National Academy of Sciences, 2001)
Studies of recombination-dependent replication (RDR) in the T4 system have revealed the critical roles played by mediator proteins in the timely and productive loading of specific enzymes onto single-stranded DNA (ssDNA) during phage RDR processes. The T4 recombination mediator protein, uvsY, is necessary for the proper assembly of the T4 presynaptic filament (uvsX recombinase cooperatively bound to ssDNA), leading to the recombination-primed initiation of leading strand DNA synthesis. In the lagging strand synthesis component of RDR, replication mediator protein gp59 is required for the assembly of gp41, the DNA helicase component of the T4 primosome, onto lagging strand ssDNA. Together, uvsY and gp59 mediate the productive coupling of homologous recombination events to the initiation of T4 RDR. UvsY promotes presynaptic filament formation on 3′ ssDNA-tailed chromosomes, the physiological primers for T4 RDR, and recent results suggest that uvsY also may serve as a coupling factor between presynapsis and the nucleolytic resection of double-stranded DNA ends. Other results indicate that uvsY stabilizes uvsX bound to the invading strand, effectively preventing primosome assembly there. Instead, gp59 directs primosome assembly to the displaced strand of the D loop/replication fork. This partitioning mechanism enforced by the T4 recombination/replication mediator proteins guards against antirecombination activity of the helicase component and ensures that recombination intermediates formed by uvsX/uvsY will efficiently be converted into semiconservative DNA replication forks. Although the major mode of T4 RDR is semiconservative, we present biochemical evidence that a conservative “bubble migration” mode of RDR could play a role in lesion bypass by the T4 replication machinery.